Double Degree Transnational Curriculum: University Internationalization Efforts in Malaysia with British Universities - Raya, Moch. Khafidz Fuad (Muslim Education Review, 2023)
Higher Education (HE) is central to advancing a nation's civilisation. In the modern context, HE has been polarised into a different practice discourse. This is the effect of globalisation which orients the neoliberal economic paradigm. This current resulted in a massive change in orientation (reform) of HE in Malaysia, which forced policymakers to internationalise HE. One of them is the transnational double degree program. British universities are considered the most suitable partners for this program due to several factors, such as the historical trajectory of British colonialism and imperialism towards Malaysia. This study uses a qualitative approach with ethnographic and documentary methods. Using the theory of "postcolonial and education" as an analysis of the findings has shown how the spectrum of colonial influence was on the education of the former colonies. Education is considered a strategy for seeding international educational networks, as in other regions. Another finding is that the originators or writers of this curriculum face a series of latent problems, such as differences in the academic and cultural climate between the two countries, different regulatory rules, and a shared credit system that still needs to be fully synchronised. This article creates a new finding that the internationalisation of HE through creating a transnational double degree curriculum is maximising HE marketing efforts amidst the current wave of globalisation competition.